Fibers by interfacial polyelectrolyte complexation – processes, materials and applications. Issue 8 (October 2016) - Wan, Andrew C.A.; Cutiongco, Marie F.A.; Tai, Benjamin C.U.; Leong, Meng Fatt; Lu, Hong Fang; Yim, Evelyn K.F.
Abstract : Interfacial polyelectrolyte (polyion) complexation (IPC) is a process whereby fibers and capsules are formed through interactions at the interface of oppositely charged polymers. Since its discovery in the late 1990s, the IPC fiber process, in particular, has been investigated for various applications such as tissue engineering, drug delivery, flexible electronics and biosensing. The advent of the IPC fiber and process has been supported by its unique mechanism of formation that makes it amenable to encapsulation and functionalization. In this first review on IPC fibers, we consolidate the current knowledge of the IPC process, mechanism of fiber formation and fiber physical properties, while documenting the various polycation–polyanion pairs and encapsulants that have been used to date. We review the rapidly accumulating literature on IPC fibers for tissue engineering, describing how they have been used to release protein factors in a sustained manner, made into random or spatially well-defined scaffolds and decorated with appropriate functionalities and extracellular matrices in order to tailor the microenvironment for cell growth and function.